Orbital fat swelling: A biomechanical theory and supporting model for spaceflight-associated neuro-ocular syndrome (SANS) - Reilly, Matthew A.; Katz, Steven E.; Roberts, Cynthia J. (Frontiers in Bioengineering and Biotechnology, 2023)
Spaceflight-Associated Neuro-ocular Syndrome (SANS) is a descriptor of several ocular and visual signs and symptoms which commonly afflicts those exposed to microgravity. We propose a new theory for the driving force leading to the development of SANS which is described via a finite element model of the eye and orbit. Our simulations suggest that the anteriorly directed force produced by orbital fat swelling is a unifying explanatory mechanism for SANS, as well as producing a larger effect than that generated by elevation in intracranial pressure. Hallmarks of this new theory include broad flattening of the posterior globe, loss of tension in the peripapillary choroid, decreased axial length, consistent with findings in astronauts. A geometric sensitivity study suggests several anatomical dimensions may be protective against SANS.